The granting of forgiveness in an intergroup context: African and Asian social representations - Etienne Mullet (2010)
The model for representing intergroup forgiveness suggested by Neto, Pinto & Mullet (2007a) has been extended through the examination of data from a large sample (n = 1036) of Asian (Cambodians and East Timorese) and African (Angolans, Guineans and Mozambicans) adults who have been personally affected by long-term wars and conflicts in their area. Exploratory and confirmatory factor analyses showed that a nine-factor model could adequately fit the whole set of data. Overall, a large majority of the participants agreed with the view that forgiveness as an intergroup process was conceivable. For a majority of the participants: (a) the aim of the intergroup forgiveness process is reconciliation with the former offender; (b) the process does not need to be strictly conditional on adequate reparation and compensation; (c) it should be democratic - in other words, forgiveness should not be decided solely by politicians, traditional or religious authorities; (d) it belongs to the forgiver-forgiven dyad - in other words, interference from the international community should be minimal; (e) it should be public (and not a negotiation between members of the elite) - forgiveness should be announced to the whole community using broad international languages; and (f) it should be an all-encompassing process, that is, it should encompass all the members of the requesting group, all the members of the forgiving group and all the offences.